The Ulica Nikite Tolstoja hodonym on the city map of Vršac (Serbia) - Marina Obizhaeva (Славянский мир в третьем тысячелетии, 2023)
This paper is devoted to the renaming of Ljubljanska street in the city of Vršac (Serbia) to commemorate Nikita Tolstoy on May 22, 2005. The paper’s author, who was then working as a Humanities Program assistant at the Russian Center of Science and Culture in Belgrade under the Russian Federation’s Ministry of Foreign Affairs, relays a memoir that references relevant media articles and describes the events which preceded this commemorative event. The memory of this outstanding philologist has become at once part of the historical and cultural legacy of his native city and the everyday context of its inhabitants thanks to the involvement of key individuals who are commemorated here.